FRI0276 Angiogenic and Anti-Angiogenic Factors in Large-Vessel Vasculitides. (9th June 2015) - Meliconi, R.; Dolzani, P.; Assirelli, E.; Pulsatelli, L.; Pipitone, N.; Muratore, F.; Pazzola, G.; Boiardi, L.; Bottazzi, B.; Mantovani, A.; Salvarani, C.
Abstract : Background: In large-vessel vasculitides (LVV), the hypoxic enviroment subsequent to stenosis of the vascular lumen is a potential signal for the generation of new blood vessels. Angiogenesis, the formation of newly-formed capillaries from pre existing vessels, may be a compensatory response to ischemia and to increased metabolic activity. Furthermore endothelial cells of newly formed vessels can cause inflammation due to the production of colony stimulation factors and chemokines for leukocyte recruitment. Angiogenesis also plays a key role in the patogenetic events leading to cronic inflammation. Angiogenic factors activate endothelial cells promoting their proliferation and migration, they also induce capillary tube formation. The balance between angiogenic and antiangiogenic factors induces and regulates the angiogenic process (1). Objectives: The purpose of this study was to analyze the amount of the angiogenic factors Vascular Endotelial Growth Factor (VEGF), FGF-2, Vascular Adesion Molecules 1 (VCAM-1), angiopoietin-1, anti-angiogenic factor endostatin and pentraxin-3 (PTX3) in the serum of patients with Giant Cell Arteritis (GCA) and Takayasu's arteritis (TA) and to correlate biomarker serum levels to: PET/TC findings, clinical indices including Indian Takayasu activity score (ITAS) and Kerr/National Institute of Health, age-matched normal control (NC) biomarker serum levels. Methods: Sera were obtained from 72 patients with LVV (33 GCA patients and 39 TA) who underwent a PET/CT scan and from 60 age-matched normal controls (NC). PET/CT scans were reviewed by a nuclear medicine physician who has no knowledge of the clinical information. Vascular uptake was graded using a 4 point semiquantitative scale. ITAS, Kerr/NIH scores and sera for serum biomarkers investigations were obtained within 20 days of the PET/CT scans. Angiogenic factor serum levels were evaluated using commercial DuoSet kits (R&D Systems) following the manufacturer's instructions. Results: Endostatin and PTX-3 serum levels were significantly higher compared to age-matched NC (Endostatin: GCA vs NC p<0.01, TA vs NC p<0.0005) Circulating levels of VEGF appeared to be significantly up-regulated only in TA patients compared to NC (p<0.005). When stratifying LVV patients according to PET/CT assessment, no difference was seen between all the investigated angiogenesis-related biomarkers levels in patients with an active scan compared to those with an inactive scan in both LVVs. In GCA patients with active disease according to clinical indices, VEGF levels were found to be significantly higher compared to inactive patients (p<0.05). In TA patients no relationship was found between serum levels of the angiogenesis-related factors tested and disease activity assessed by clinical indices. Conclusions: The results highlight an imbalance in the production of positive and negative regulatory factors in the angiogenic response in LVV. In addition, VEGF seems to differentially contribute to the definition of the GCA and TA angiogenic profiles. References: Maruotti N et al, Clin Exp Rheumatol 2008 Disclosure of Interest: None declared